Answer: n=-7
Step-by-step explanation:
3n-7=6n-2n
3n-7=4n
-7=n
n=-7
Answer:
Simplifying 9m + -3 + -7m = 0
Reorder the terms: -3 + 9m + -7m = 0
Combine like terms: 9m + -7m = 2m -3 + 2m = 0 Solving -3 + 2m = 0
Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right.
Add '3' to each side of the equation. -3 + 3 + 2m = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 2m = 0 + 3 2m = 0 + 3 Combine like terms: 0 + 3 = 3 2m = 3
Divide each side by '2'. m = 1.5
Step-by-step explanation:
Hope this helps :)
Where is the table? I need to see a table to give the answer
(2y +1)(4y + 1) is the factored form
Answer:
The answer will be 64.5
Step-by-step explanation: